Calculating Groundwater Recharge Using Water Balance in Mandaly City, Diyala Governorate, Eastern Iraq - Al-Mashhadani, Reham Basim; Al-Kubaisi, Qusai Y. (Iraqi Journal of Science, 2023)
Water balance approaches are strategies for resolving key theoretical and practical hydrological issues. The major goals of this study are to examine climatic elements and conditions to calculate groundwater recharge using the water balance approach. The study area is located in Mandaly city, Diyala Governorate, eastern Iraq. The metrological data was gathered between 1994 and 2020 to evaluate the study area's climate. The annual rainfall rate has been 248.61 mm, with a relative humidity of 43.89%, a temperature of 24.41 oC, a wind speed of 1.99 m/sec, sunshine of 8.32 hours per day, and evaporation of (268.09 mm). The total amount of corrected evapotranspiration was 1010.09 mm, with a peak value of 225.29 mm in July and the lowest value of 3.91 mm in January. the climate was classified into arid and sub-arid. The water surplus (WS) has been calculated to be 149.52 mm and 60.14 % annual rainfall. The surface runoff is 24.86mm, and the groundwater recharge value is 124.66 mm with a rate of 50.14 %. This shows the percentage of groundwater recharge from total rainfall.